Ramsey monetary policy and international relative prices - Ester Faia; Tommaso Monacelli (European Central Bank (ECB), 2004)
We analyze welfare maximizing monetary policy in a dynamic two-country model with price stickiness and imperfect competition. In this context, a typical terms of trade externality affects policy interaction between independent monetary authorities. Unlike the existing literature, we remain consistent to a public finance approach by an explicit consideration of all the distortions that are relevant to the Ramsey planner. This strategy entails two main advantages. First, it allows an accurate characterization of optimal policy in an economy that evolves around a steady-state which is not necessarily efficient. Second, it allows to describe a full range of alternative dynamic equilibria when price setters in both countries are completely forwardlooking and households' preferences are not restricted. In this context, we study optimal policy both in the long-run and along a dynamic path, and we compare optimal commitment policy under Nash competition and under cooperation. By deriving a second order accurate solution to the policy functions, we also characterize the welfare gains from international policy cooperation.
Keywords: E52; F41; 330; Cooperation; imperfect competition; Nash equilibrium; optimal monetary policy; Ramsey planner; sticky prices